A reduced switching frequency capacitor voltage balancing control for modular multilevel converters. (November 2022) - Luo, Yongjie; Jia, Zan; Xu, Luona; Li, Qifen; Song, Yonghui
Highlights: In this paper, the sub-module switching process and the capacitor voltage sequence of a modular multilevel converter arm is analyzed. A method to predict the capacitor voltage convergence in the next control cycle based the voltage sequence is proposed, which can remarkably improve the utilization of switching occurrences and reduces the average switching frequency. Based on the predicted voltage sequence, an improved capacitor voltage balancing method is proposed, which can significantly reduce the additional switching loss and improve the operating efficiency of the converter system. Abstract: Modular multilevel converter (MMC) is one of the most promising topologies in high/medium-voltage applications, but high switching losses impair system economy and reliability. For the high-voltage MMC with the nearest level modulation (NLM), there is usually high frequency and uncertain switching actions among submodules (SMs) in each arm, due to the traditional sorting based capacitor voltage balancing control method, which brings additional power losses. In order to solve this problem, the SM switching process and the capacitor voltage sequence of a MMC arm is analyzed, and then a method to predict the capacitor voltage convergence in the next control cycle is proposed in this paper. Based on the predicted voltage sequence, an improved capacitor voltage balancing method is proposed, which can significantly reduce the additional switching loss and improve the operating efficiency of the converter system. MATLAB/simulink simulation and RT-LAB based HIL test results verify the proposed method under different operating conditions.